E-commerce brand: The effect of perceived brand leadership on consumers' satisfaction and repurchase intention on e-commerce websites. Issue 6 (10th May 2019) - Chiu, Weisheng; Cho, Heetae
Abstract : Purpose: The purpose of this paper is to investigate the influence of perceived brand leadership of an e-commerce website on satisfaction and repurchase intention. Moreover, the different roles of gender and age were explored in the proposed model. Design/methodology/approach: An online survey was administered to Chinese consumers ( n =476) who have purchased products on e-commerce websites. Using SmartPLS 3.0 software, a partial least squares structural equation modeling analysis was conducted in this study. Findings: The results showed that all factors of perceived brand leadership (i.e. quality, value, innovativeness and popularity) have positive influences on satisfaction, and in turn satisfaction significantly affects repurchase intention. Also, value and popularity have positive influences on repurchase intention. In addition, gender differences were found in the proposed model. More specifically, the influence of quality on satisfaction was stronger for male consumers, while the impact of popularity on satisfaction was stronger for female. In terms of age differences, the influence of quality on satisfaction was stronger for the consumers over 40 years old as compared to the younger consumers (i.e. the 20s). Moreover, the influence of innovativeness on satisfaction and repurchase intention was stronger for the 20s consumers as compared to the consumers who are over 40 years old. Originality/value: This study attempts to apply the concept of brand leadership to the e-commerce setting by addressing differential consumption decision-making process. In addition, different gender and age groups reveal unique preferences and consumption patterns.